3x=32.27
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(-32).74-32.27+32
=32.(-74)-32.27+32
=32.[(-74)-27+1]
=32.(-100)
=-3200
\(-32\cdot74-32\cdot27+32\)
\(=32\left(-74-27+1\right)\)
\(=32\cdot\left(-100\right)\)
=-3200
32.27 + 47.73 + 27.15
= (32.27+27.15)+47.73
=27.(32+15)+47.73
= 27.47 + 47.73
= 47.(27+73)
= 47. 100
=4700
32.27+154.69+73.32-69.54
= 32.27+73.32+154.69-69.54
= 32.(27+73)+(154-54).69
= 32.100 + 100.69
= (32+69).100
= 101.100
= 10100
32.27+154.69+73.32-69.54
=(32.27+73.32)+(69.154-69.54)
=32.100+69.100
=3200+6900
=10100
\(2.21.18+12.9+76.36\)
\(=36.21+36.3+76.36\)
\(=36.\left(21+3+76\right)\)
\(=36.100=3600\)
`a, (3x-1)^3-(3x+1)^3`
`= (3x-1-3x-1)(9x^2-6x+1+9x^2-1+9x^2+6x+1`
`= (-2)(27x^2 +1)`
`= -54x^2-2`.
`b, (1+3x)^3 - (1-3x)^3`
`= 1+ 9x + 27x^2 + 27x^3 - 1 + 9x - 27x^2 + 27x^3`
`= 54x^3 + 18x`.
`c, = 54x^3 + 18x -1 +9x^2`.
a: =27x^3-27x^2+9x-1-27x^3-27x^2-9x-1
=-54x^2-2
b: =27x^3+27x^2+9x+1-27x^3+27x^2-9x+1
=54x^2+2
c: =54x^2+2+(3x-1)(3x+1)
=54x^2+2+9x^2-1
=63x^2+1
Em kiểm tra lại đề bài, \(3^x+3^{x+2}+3^{x+2}\) hay \(3^x+3^{x+1}+3^{x+2}\)
=>3x=32.33
=>3x=35
=>x=5
=>3^x=3^2.3^3
=>3^x=3^5
=>x=5